Complement protein and Immunoglobulins Serum levels in Normal Pregnant and Spontaneous Aborted Women - Abdulrahman Ahmad, Hiwa; Muhammd salih, Mehri Mirhaj; Ahmed Khidir, Kamal (Kurdistan Journal of Applied Research, 2018)
Disorder of maternal immune responses during pregnancy triggers immunological rejection of fetus antigens by maternal immune components, contribute to spontaneous abortion or miscarriage. The study was designed to concentrated on immunoglobulins (IgM, IgG and IgA) and complement elements (C3 and C4) serum levels changes in normal pregnant and abortion women. Study groups were classified into normal pregnant women (20), spontaneous abortion (30) and non-pregnant women (16) as a control group, attending to Shahid Dr. Khalid Hospital/Department of Gynecology and Obstetrics/Koya city. Serum levels of immunoglobulins (IgG, IgM, and IgA), complement proteins (C3 and C4) were determined and analyzed for normal pregnant, abortion and control groups by using Single Radial Immunodiffusion (SRID) technique. The results demonstrated that concentration of IgG levels in abortion differed significantly in compare to normal pregnancy (p ?0.05), while there were no significant differences in IgM and IgA serum levels among groups (p >0.05). Also, statistical analysis revealed that serum levels of C3 and C4 significantly decreased in abortion group compared to normal pregnant and non-pregnant groups (p ?0.05). Concluded that complement proteins (C3 andC4) are a good defense line during normal pregnancy, sometime activation (hyper-consuming) of complement elements may provoke spontaneous abortion, while immunoglobulins are a little role in inducing of miscarriage in pregnant women.